818. Understanding Current Practices of an Electronic Antimicrobial Resistant Organism (ARO) Screening Tool Used in Healthcare Facilities in Alberta, Canada. (4th December 2021) - Leal, Jenine; Versluys, Kristen; Pfister, Ted; Ellison, Jennifer; Bush, Kathryn; Pitchko, Janice; Woolsey, Samantha; Vayalumkal, Joseph V; Lee, Bonita; Smith, Stephanie; Kim, Joseph; May, Elissa Rennert
Abstract: Background: Increasing antibiotic resistance is a global problem. By detecting individuals colonized with antimicrobial resistant organisms (AROs) through hospital admission screening, enhanced precautions can be implemented to interrupt transmission during their hospitalization. The objective is to understand current practices of ARO screening in Alberta hospitals by evaluating completeness of an electronic ARO screening tool. Methods: A retrospective cohort study using electronic medical record (EMR) data from Connect Care (Epic Systems Corp.) at one adult and one pediatric tertiary hospital in Edmonton, Alberta between January 1, and December 31, 2020 was conducted. All hospital admissions were included. Outcomes included proportion of admissions with a completed ARO tool and a comparison of the best practice actions triggered (e.g. ARO screening swab and/or isolate) between those with and without a completed ARO tool. Test of proportions was used, with a two-sided α of 0.05 and was conducted using STATA/SE 16.1. Results: During the study period, there were 32, 600 total admissions, of which 16, 342 (50.1%) had the ARO tool completed. The overall compliance was greater in the adult hospital (53.9%) compared to the pediatric hospital (36.3%) (< 0.001). For both hospitals, the compliance rate in December 2020 was 30.0% lower than in January 2020, with a continuous decline during the 12 months. An isolation order or screening swab was ordered in 40.6% of admissions without an ARO tool completed compared to 56.5% of admissions with the ARO tool completed. Based on responses in the completed ARO tool, 81.2% of patient admissions had a microbiologic swab ordered when indicated, of which only 4.7% were positive. However, only 35.9% of patient admissions had additional precautions ordered when indicated. Conclusion: ARO screening is a required organizational practice and although standardized across all Alberta hospitals and embedded within an EMR, compliance was poor. Further work is needed to understand point-of-care risk assessment processes to inform future interventions aimed at early identification and decreased transmission of ARO in hospitals. Disclosures: All Authors : No reported disclosures